Calpain-1 weakens the nuclear envelope and promotes the release of neutrophil extracellular traps - Singh, Jeeshan; Zlatar, Leticija; Muñoz-Becerra, Marco; Lochnit, Günter; Herrmann, Irmgard; Pfister, Felix; Janko, Christina; Knopf, Jasmin; Leppkes, Moritz; Schoen, Janina; Muñoz, Luis E.; Schett, Georg; et al. (Cell communication and signaling, 2024)
The inducers of neutrophil extracellular trap (NET) formation are heterogeneous and consequently, there is no specific pathway or signature molecule indispensable for NET formation. But certain events such as histone modification, chromatin decondensation, nuclear envelope breakdown, and NET release are ubiquitous. During NET formation, neutrophils drastically rearrange their cytoplasmic, granular and nuclear content. Yet, the exact mechanism for decoding each step during NET formation still remains elusive. Here, we investigated the mechanism of nuclear envelope breakdown during NET formation. Immunofluorescence microscopic evaluation revealed a gradual disintegration of outer nuclear membrane protein nesprin-1 and alterations in nuclear morphology during NET formation. MALDI-TOF analysis of NETs that had been generated by various inducers detected the accumulation of nesprin-1 fragments. This suggests that nesprin-1 degradation occurs before NET release. In the presence of a calpain-1, inhibitor nesprin-1 degradation was decreased in calcium driven NET formation. Microscopic evaluation confirmed that the disintegration of the lamin B receptor (LBR) and the collapse of the actin cytoskeleton occurs in early and later phases of NET release, respectively. We conclude that the calpain-1 degrades nesprin-1, orchestrates the weakening of the nuclear membrane, contributes to LBR disintegration, and promoting DNA release and finally, NETs formation.